2011
DOI: 10.1016/j.neuroscience.2011.05.067
|View full text |Cite
|
Sign up to set email alerts
|

Fear conditioning is associated with dynamic directed functional interactions between and within the human amygdala, hippocampus, and frontal lobe

Abstract: The current model of fear conditioning suggests that it is mediated through modules involving the amygdala (AMY), hippocampus (HIP), and frontal lobe (FL). We now test the hypothesis that habituation and acquisition stages of a fear conditioning protocol are characterized by different event-related causal interactions (ERC) within and between these modules. The protocol employed the painful cutaneous laser as the unconditioned stimulus and ERC was estimated by analysis of local field potentials recorded throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 71 publications
(104 reference statements)
1
30
0
Order By: Relevance
“…The terms "gamma band (Ͼ30 Hz)" or "40 Hz" have often been used to describe synchronous neuronal signals. However, the actual frequency ranges showing synchronization between neurons in different structures are variable and are mostly in the range of 20 -60 Hz, which includes the activity below the gamma band (Engel (Andres et al 1999;Classen et al 1998;Mima et al 2001;von Stein et al 1999), subdural electrodes (Ohara et al 2001(Ohara et al , 2004, and depth electrodes (Liu et al 2011a;Tallon-Baudry et al 2001). Therefore, synchronous oscillations are not necessarily limited to the gamma band or to particular cortical structures, especially in the case of large-scale synchrony.…”
Section: Discussionmentioning
confidence: 99%
“…The terms "gamma band (Ͼ30 Hz)" or "40 Hz" have often been used to describe synchronous neuronal signals. However, the actual frequency ranges showing synchronization between neurons in different structures are variable and are mostly in the range of 20 -60 Hz, which includes the activity below the gamma band (Engel (Andres et al 1999;Classen et al 1998;Mima et al 2001;von Stein et al 1999), subdural electrodes (Ohara et al 2001(Ohara et al , 2004, and depth electrodes (Liu et al 2011a;Tallon-Baudry et al 2001). Therefore, synchronous oscillations are not necessarily limited to the gamma band or to particular cortical structures, especially in the case of large-scale synchrony.…”
Section: Discussionmentioning
confidence: 99%
“…Pavlovian classical conditioning is commonly used to study contextual fear learning [39,40]. This test clearly demonstrated that male AD mice had better learning and memory than female mice, and VPA treatment improved the learning and memory of the AD mice with gender differences.…”
Section: Discussionmentioning
confidence: 99%
“…Here we briefly describe ERC methods that have already been described in detail in previous reports (Boatman-Reich et al 2010; Korzeniewska et al 2003Korzeniewska et al , 2008Liu et al 2011aLiu et al , 2011b). …”
Section: Event-related Causalitymentioning
confidence: 99%
“…We have now tested the hypothesis that attention to the laser stimulus is associated with increased EEG functional interactions involving widespread cortical structures, which are different from the structures associated with attention to a nonpainful electrical stimulus. The widespread functional interactions were quantified by the event-related causality (ERC), an approach that has previously been used to study event-related interactions among brain areas (Boatman-Reich et al 2010;Korzeniewska et al 2003Korzeniewska et al , 2008Liu et al 2011aLiu et al , 2011b. As a corollary of this hypothesis, we tested whether the analysis of the EEG would show evidence of pain-related ERC interactions characteristic of critical sites.…”
mentioning
confidence: 99%